Expert System For Cupping Treatment Using Case Based Reasoning Method - Evi Dewi Sri Mulyani; Rahadi Deli Saputra; Rais Mujahidul Haq (CCIT (Creative Communication and Innovative Technology) Journal, 2020)
Cupping is one of the methods of treatment taught by Rasulullah SAW (thibbun nabawi) which can be believed to be a cure because it is sourced from revelations that are certain, divine powers with the perfection of reason. Rasulullah SAW said: "Every disease has a cure. So if the drug is about an illness, the disease will be cured with the permission of Allah SWT. (HR. Muslim), cupping is the best choice for treatment, because it is cheap, lawful, safe, practical and follows the sunnah of Rasulullah SAW. If cupping is done properly and correctly, according to medical rules. With the limited knowledge and memory of the therapist in determining the location of the cupping point can be an error because if there is a new symptom or with a new disease that has never been overcome by a therapist becomes one of the obstacles in determining the location of the cupping point quickly and accurately. so the need for the application of an expert system that can facilitate the cupping therapists to determine the location of the cupping point to patients precisely and quickly. Expert system that will be created using a case based reasoning method. The implementation of the system uses the PHP programming language and MySQL database. With an expert system that uses the case-based reasoning method of cupping treatment can determine the cupping point precisely in accordance with the symptoms that are inputted to be processed into output in the form of solutions to overcome the disease by displaying conclusions in the form of cupping points so as to facilitate the services performed by therapist.